Physical and Chemical Factors Affecting biomass and alpha toxin production of CLOSTRIDIUM PERFRINGENS TOXINOTYPE A - M. Tariq; A. A. Anjum; A. A. Sheikh; A. R. Awan; M. M. K. Sattar; T. Ali; M. Nawaz (Journal of Animal and Plant Sciences, 2022)
Clostridium perfringens toxinotype A is one of the important causes of diarrhea/enterotoxaemia in small and large ruminants. Various vaccines have been used against it in Pakistan but all are imported. To muddle through frequent onset of disease present study was conducted to optimized the various physical and chemical factors for maximum production of biomass and alpha toxin of C. perfringens type A. Biochemically confirmed indigenous isolates (n=3) were characterized by 16S rRNA gene amplification, followed by sequencing. These sequences were submitted in GenBank by the following accession no: MW332257.1, MW551947.1 and MW471067.1. Toxinotype A was confirmed by amplification of alpha-toxin gene and sequenced. Biomass and alpha-toxin were optimized for various physical (pH, time, and temperature) and chemical (carbohydrates, vitamin, mineral mixture, tween 80, ammonium chloride, sodium and potassium salts) parameters. Higher biomass was produced by MW551947.1 at 37°C with 7.5 pH (60.58±1.11 mg/mL) of RCM broth and at 0.5% sodium chloride (34.51±0.50 mg/mL) concentration for optimization after 48 hours of incubation. Furthermore, higher hemolytic units of alpha-toxin were produced by MW551947.1 at 37°C (6.07±0.12 HU/mL) and 0.3% glucose (47.73±0.23HU/mL) concentration with 6.5pH of broth after 24 hours of incubation. Under these optimized parameters, maximum biomass and alpha-toxin may be produced for cost-effective vaccine production on commercial basis.
Keywords: Alpha toxin; Biomass; Glucose; r RNA; Sodium chloride; Toxinotype A